Search 83,401 tutors
FIND TUTORS
Ask a question
0 0

Indice question?

Tutors, please sign in to answer this question.

1 Answer

32x - 10(3x) + 9 = 0
 
(3x)2 - 10(3x) + 9 = 0               [32x = (3x)2]
 
Let u = 3x
 
u2 - 10u + 9 = 0
 
Factors to:
 
(u-9)(u-1) = 0
 
u = 9, 1
 
u = 3x = 9, so x = 2              [32=9]
u = 3x = 1, so x = 0              [30=1]

Comments

Hi Philip,
 
Very good answer, but one minor point -- your second line has 10(3x); I think it should be 10(3x).
 
Regards, Pete
Fixed.  Thanks, Pete.